2021
DOI: 10.1111/jocn.15861
|View full text |Cite
|
Sign up to set email alerts
|

Nurse bias and nursing care disparities related to patient characteristics: A scoping review of the quantitative and qualitative evidence

Abstract: Introduction: Investigations of healthcare workers' implicit attitudes about patient characteristics and differences in delivery of healthcare due to bias are increasingly common.However, there is a gap in our understanding of nurse-specific bias and care disparities. Aims:To identify (a) the types of available evidence, (b) key factors and relationships identified in the evidence and (c) knowledge gaps related to nurse bias (nurse attitudes or beliefs towards a patient characteristic) and nursing care dispari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Black, hispanic and other ethnicities were less likely to have missing data when compared with their Caucasian counterparts, which may be explained by nursing staff bias to obtain location data disproportionately based on ethnicity. 27 Patients arriving via Flight for Life (or any helicopter-based transportation) were significantly more likely to have missing location information. Patients requiring air transportation are usually critically ill, medically complex and require life-saving intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Black, hispanic and other ethnicities were less likely to have missing data when compared with their Caucasian counterparts, which may be explained by nursing staff bias to obtain location data disproportionately based on ethnicity. 27 Patients arriving via Flight for Life (or any helicopter-based transportation) were significantly more likely to have missing location information. Patients requiring air transportation are usually critically ill, medically complex and require life-saving intervention.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that most research regarding bias and implicit bias was focused on errors in diagnostic decision-making in physicians; however, they identified limited research that demonstrated how bias can impact nurses' assessment and treatment of pain, patient triage, and recognition of clinical deterioration. Groves 20…”
Section: Biasmentioning
confidence: 99%
“…They noted that most research regarding bias and implicit bias was focused on errors in diagnostic decision-making in physicians; however, they identified limited research that demonstrated how bias can impact nurses' assessment and treatment of pain, patient triage, and recognition of clinical deterioration. Groves 20 published a comprehensive scoping review that explored bias in nursing care to identify interventions to reduce associated healthcare disparities. Of 215 studies screened, only 2 identified interventions that addressed racial bias among nurses.…”
Section: Biasmentioning
confidence: 99%
“…Stigmatizing attitudes towards individuals experiencing homelessness are pervasive, including within the nursing profession (Zeien et al, 2021). In their scoping review, Groves et al (2021) found that nurses share the general public's negative perceptions against marginalized social groups, such as the homeless population, impacting the quality of care provided. These stigmatized communities were found to receive inferior healthcare treatment with shorter nurse-patient interaction time, poorer communication, and suboptimal pain management (Groves et al, 2021).…”
Section: Understanding What the Problem Is Represented To Bementioning
confidence: 99%